Increased interleukin 8 expression in the colon mucosa of patients with inflammatory bowel disease. Issue 2 (February 1996) - Daig, R; Andus, T; Aschenbrenner, E; Falk, W; Schölmerich, J; Gross, V
Abstract : To test whether there is a difference in the expression of interleukin 8 (IL8) between Crohn's disease and ulcerative colitis and to determine the main site of its synthesis this study analysed IL8 in mucosal biopsy specimens of patients with Crohn's disease and ulcerative colitis by enzyme linked immunosorbent assay (ELISA) and by in situ hybridisation. IL8 was measured by ELISA in 38 normal control patients, eight inflammatory control patients, 55 Crohn's disease biopsy specimens (26 patients), and 67 ulcerative colitis biopsy specimens (35 patients). IL8 mRNA was determined in samples by in situ hybridisation using a specific IL8 RNA probe. IL8 protein was significantly increased in macroscopically inflamed specimens of Crohn's disease (median 118 pg/specimen, p < 0.0001), ulcerative colitis (median 140 pg/specimen, p < 0.001), and inflammatory controls (median 30 pg/specimen, p = 0.010) compared with normal controls (median 4 pg/specimen). IL8 was also increased in uninflamed specimens of Crohn's disease (median 46 pg/specimen, p < 0.001) but not of ulcerative colitis patients (median 9 pg/specimen, p = 0.3). IL8 protein in the mucosa correlated significantly with macroscopic inflammation in Crohn's disease (r = 0.47, p < 0.001) and in ulcerative colitis (r = 0.60, p < 0.001). IL8 mRNA was detected by in situ hybridisation in 31 of 55 biopsy specimens (56%) of Crohn's disease patients, in 38 of 67 specimens of ulcerative colitis patients (57%), in five of eight inflammatory controls (63%) and in five of 38 normal controls (13%). Mucosal IL8 mRNA expression correlated with mucosal IL8 protein (r = 0.46, p < 0.001). IL8 mRNA was only detected in inflammatory cells of the interstitium but not in mucosal epithelial cells. IL8 is produced mainly in the lamina propria of the colon in inflammatory bowel disease and correlates with mucosal inflammation.